Xylitol formation and reduction equivalent generation during anaerobic xylose conversion with glucose as cosubstrate in recombinant Saccharomyces cerevisiae expressing the xyl1 gene. - Thestrup, H N (1995)
Glucose was used as a cosubstrate under anaerobic conditions in the conversion of xylose to xylitol by a recombinant Saccharomyces cerevisiae strain expressing the xyl1 gene. Glucose was metabolized mainly through glycolysis, with carbon dioxide, acetate, and ethanol as end products and with reduction equivalents generated in the glyceraldehyde-3-phosphate dehydrogenase and acetaldehyde dehydrogenase reactions. At a high glucose supply rate, generation of surplus reduction equivalents resulted in simultaneous ethanol formation. On the other hand, at a low glucose supply rate, additional reduction equivalents were generated by simultaneous ethanol consumption. A significantly lower xylitol formation rate was observed.